Kyrgyzstan's New Degree System - Merrill, Martha; Ryskulova, Chynara (International Higher Education, 2012)
Kyrgyzstan is replacing Soviet-era degrees with Bachelor's and Master's degrees, and contact hours with credit hours. This aligns Kyrgyzstan's higher education system with those of neighboring nations that have been accepted into the Bologna Process. However, many problems are likely to arise, because few educators, students, parents, or employers fully understand the new system and resources available to implement it are minimal.